HYPERDENSE BASILAR ARTERY SIGN IN ISCHEMIC STROKE PATIENT WITH COVID-19: A CASE REPORT - Asrini, Neoniza Eralusi; Umam, David Noor (MNJ (Malang Neurology Journal), 2024)
Background: Coronavirus disease 2019 (COVID-19) can cause coagulopathy, leading to thromboembolism disease such as ischemic stroke. Ischemic stroke due to basilar artery occlusion (BAO) is rare condition, which is hard to diagnose and has high mortality especially if accompanied by COVID-19. Objective: To evaluate the presence of infarction in the basilar area in COVID-19 patients and prevent complications that arise due to misdiagnosis Methods: 41 year old male patient came to the emergency unit with left-side weakness, slurred speech, vertigo, and nausea 7 hours before admission. He also had mild fever, cough, and fatigue a week before admission. Patient had full consciousness, blood pressure 180/100, left hemiparesis (motoric 3/5), dysarthria, dysphagia. His National Institutes of Health Stroke Scale (NIHSS) score was 7. Results: From laboratory examination, neutrophil lymphocyte ratio (NLR) was increased to 3.60, he tested positive for SARS-CoV-2 rapid antigen and Polymerase Chain Reaction (PCR) with cycle threshold (CT) value 28.66, and D-dimer was increased to 4000 ng/mL. Bronchovascular markings increased on chest X-ray and hyperdense bacillary artery sign found on head CT-scan suggesting vertebrobasilar infarct.  Acute stroke ischemic due to large vessel occlusion in COVID-19 found more often in young men with mild symptoms or asymptomatic COVID-19. Prodromal symptoms and stroke onset in BAO can be atypical and variable. Hyperdense bacillary artery sign on head CT scan was a specific sign and can support the diagnosis of BAO. Concussion: Patient’s condition got better progressively and was allowed to discharge from hospital after 6 days. BAO patients with younger age, lower NIHSS scores, early diagnosis, and prompt treatment had better prognosis.